Coherent all-optical reservoir computing for nonlinear equalization in long-haul optical fiber communication systems - Peng, Guanju; Liu, Yaping; Li, Zheng; Zhu, Kunpeng; Yang, Zhiqun; Li, Jianping; Zhang, Shigui; Huang, Zhanhua; Zhang, Lin (Optics and laser technology, 2024)
•A reservoir computing (RC) is operated optically without O/E/O conversion.•The all-optical RC mitigates nonlinear distortion in a 3960-km fiber link.•Phase property enhances the RC’s performance in nonlinear signal processing.•The RC improves the Q2 factor by 2.6 dB in a single-λ system and 1.9 dB in a WDM system. Photonic reservoir computing (RC), as a promising paradigm of optical signal processing, has attracted a great deal of attention in fiber nonlinearity equalization recently. For real long-haul transmission scenarios, we propose an all-optical RC operated in a coherent scheme to mitigate the nonlinear distortion of high-speed signals. Compared with the direct decision architecture, the proposed RC can dramatically improve the Q2 factor by 2.6 dB for a single-wavelength system and 1.9 dB for a 7-channel wavelength-division multiplexing (WDM) system over 3960-km fiber transmission. Furthermore, the robustness of the coherent all-optical RC is also verified by conducting studies on different training sequences. The coherent all-optical RC shows great potential in real-time nonlinearity mitigation for long-haul fiber transmissions.